Varieties of Recursivity in Transnational Governance. Issue 3 (11th September 2017) - Malets, Olga; Quack, Sigrid
Abstract: This special section analyzes the variety of recursivity in transnational regulatory governance. We conceptualize recursivity as a complex cycle through which addressees' response to transnational rules continuously feeds back into the rulemaking process and triggers rule revision. In the introduction to the special section, we emphasize that recursivity varies across governance organizations and governance fields and develop an analytical framework to capture this variation. We also propose a typology of recursive governance organizations. Finally, we preview five case studies included in the special section and summarize their key findings and conclusions, with particular attention to the implications for accountability and legitimacy. Abstract : Mapping different forms of feedback and building a typology of varieties of recursivity allows for a better informed evaluation of the accountability and legitimacy of transnational governance.